Across divides: art, women, and politics in the remaking of Germany after 1945 - Mendelsohn, T (2024)
Art as dissent or as propaganda: these models have governed understandings of art, politics, and society in both postwar Germanies, and they have been gendered masculine. This dissertation reveals another model: art as education for making society. This model was gendered female and dominated by women after 1945 in divided Germany. German men and politics had failed. Art and women could come to the fore, articulate fundamental problems, and test out solutions from the 1940s through the 1960s. How could the Germans be reformed to comprise a new society? What pasts could be made usable for this and how? Art was a key medium because it was a system unto itself and remained intact across the divides. Each chapter shows how Germany was not foreordained as ‘East’ and ‘West’, FRG and GDR, but tested out on the basis of a common and fragmented past. Chapter 1 focuses on women’s marginality as an opportunity for society-making and how artists reframed their different pasts across 1945 to enable this. Chapter 2 moves from artists to women in the arts, focusing on a leading critic, who turned the category of women’s art into a programme of postwar reconstruction and making the public by remaking the domestic sphere through contemporary art. Chapter 3 examines canon-making for new societies, as it was practised in different ways by women before, during, and after the war. Chapter 4 presents three case studies of the empowered postwar woman in the arts: making policy, founding a museum, or holding a national commission. Chapter 5 explores how new German histories were constructed through exhibitions in the West and artistic oeuvres in the East. Altogether, the dissertation shows how ‘postwar’ German history can and must be told from before 1945 and as one, with women at the core.